2020
DOI: 10.5334/gh.779
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Abdominal Waist Circumference and Blood Pressure In Brazilian Adolescents With Normal Body Mass Index

Abstract: Obesity is the most common chronic disease in adolescents. In adults, waist circumference (WC) is associated with the presence of cardiovascular risk factors and is also a better predictor of cardiovascular (CV) risk than body mass index (BMI). The association between WC and CV risk factors in adolescents has been poorly explored so far, mainly in those within the normal BMI range. Objective: To evaluate the association between WC and elevated blood pressure (BP) in adolescents with a normal BMI. Methods: Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
3
9
0
2
Order By: Relevance
“…Risks increased up to 8 times with abdominal adiposity indicators. Our findings were similar to those reported by Pausova et al (2012) and Pazin et al (2020), where an association was found between adolescents abdominal adiposity and high BP, especially among in boys [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Risks increased up to 8 times with abdominal adiposity indicators. Our findings were similar to those reported by Pausova et al (2012) and Pazin et al (2020), where an association was found between adolescents abdominal adiposity and high BP, especially among in boys [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Data collection was performed in schools by qualified and standardised healthcare professionals. Assessments were carried out under standardised conditions and according to the protocol collected in the Data Collection Procedure Manual, which was specifically developed for the Childhood Obesity Surveillance Initiative (COSI) [ 25 ]. To measure height and body weight, participants removed their shoes and socks and any heavy clothing or accessories.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a relationship between waist circumference and skinfolds with increased blood pressure has been observed in children [ 23 ]. Therefore, supplementing waist circumference with hip circumference, waist-to-hip ratio, neck circumference, and skinfolds could be used to predict cardiovascular risk [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, o IMC não é capaz de avaliar as transformações ocorridas na composição corporal, principalmente durante a adolescência 40 . Assim, medidas adicionais como a CC e a RCEst são de grande utilidade para avaliação da adiposidade abdominal, uma vez que avalia a distribuição da gordura corporal, a qual está mais associada a fatores de risco cardiovascular [40][41][42] .…”
Section: Anounclassified